Analysis of Effective Marketing Strategies in Facing Tight Competition in the Marketplace Global - Salam, Karta Negara; Aslim, Sandi; Palinggi, Prudence Patricia Hieroploise; Marsela, Ibrahim; Megawaty, Megawaty (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aims to analyze the effectiveness of marketing strategies in addressing intense global competition, focusing on digital transformation, differentiation, and adaptive strategies. It examines how artificial intelligence (AI), big data analytics, and omnichannel marketing enhance customer engagement and competitive advantage. Additionally, it explores challenges small and medium enterprises (SMEs) face in global markets and evaluates key performance indicators (KPIs) for marketing effectiveness. This study adopts a systematic literature review (SLR) approach, synthesizing findings from existing academic research on global marketing strategies. The research integrates theoretical frameworks such as Porter’s Competitive Advantage theory and digital transformation models to assess how businesses leverage AI, data analytics, and innovative marketing techniques. Relevant literature from credible sources, including Emerald, Elsevier, Wiley, and Springer, is analyzed to identify trends and practical insights. The findings highlight that AI-driven marketing and data analytics enhance precision in market segmentation, real-time engagement, and personalization. Differentiation through innovation, branding, and omnichannel marketing is critical for maintaining competitive positioning. While SMEs face resource constraints, digital strategies like SEO and social media marketing offer cost-effective, competitive tools. However, barriers such as high technology adoption costs and resistance to change must be addressed for successful digital transformation. This study provides practical insights for businesses to adopt data-driven marketing strategies, enhance brand positioning, and optimize marketing investments. It offers recommendations for policymakers and industry leaders on fostering digital adoption and innovation to sustain competitiveness.